Esan Response to Benin Draconian Legislation in Pre-Colonial times: Historical Lessons in Secession for Modern Nigeria - Orukpem, Williams Ehizuwa (Àgídìgbo: ABUAD Journal of the Humanities, 2020)
This paper examines secessionism as a problem of Nation and State building in Nigeria. It chronicles the warning historical lessons inherent in the 15th century Esan secession from Benin among others. Since the end of Nigerian civil war in 1970, the study finds that the threat of secession has continued to haunt the country. Political highhandedness and economic marginalisation in modern Nigeria have fueled secessionist tendencies beyond the pre-1967 level. More so, the frustrations and grievances of disgruntled Nigerians against the State are being expressed in militancy, terrorism, and other acts of criminalities that erode peace and unity. In the circumstance, nationalism has become the opportunity cost of maladministration and corruption in Nigeria. Therefore, the study juxtaposes the causations of revolution and secession in history with current happenings in Nigeria. And it concludes that there is a strong re-birth of injustice and oppression; which makes the threat of disintegration plaguing Nigeria very real. Consequently, the paper demonstrated the utility of historical knowledge as a political compass for guiding leadership in Nigeria to eschew past mistakes that bred secession.